STRATEGI KOMUNIKASI PEMASARAN BERKAH LAUNDRY DALAM MENARIK DAN MEMPERTAHANKAN PELANGGAN - Melita, Yerah (Jurnal Insani, 2025)
In the current state of Indonesia's unstable economy, influenced by various factors such as high inflation, declining investor confidence, and increasing production costs, many companies have been forced to lay off employees. The impact of these layoffs is significant, particularly on the welfare of workers and their families. To meet their daily needs, some individuals have turned to entrepreneurship, one of which is in the laundry service sector. This type of business is considered promising due to the high mobility of society, which limits the time people have for household chores such as washing and ironing clothes. The proliferation of laundry businesses has led to intense competition, making it essential to implement effective marketing communication strategies to attract consumers and maintain customer loyalty. This study aims to explore the marketing communication strategies employed by Berkah Laundry in facing such competition. The researcher utilizes the marketing mix theory as the theoretical foundation and adopts a qualitative approach with purposive sampling techniques. Data collection methods include observation, interviews, and documentation, with triangulation of sources, techniques, and time used for data validation. The findings indicate that Berkah Laundry applies marketing communication strategies through promotional pricing, discounts, special packages, and timely service. Additionally, the clean, neat, and fragrant laundry results add further value. In terms of the promotion mix, the strategies used include advertising, personal selling, and sales promotions.